STRUKTUR KOMUNITAS DAN NILAI KONSERVASI IKHTIOFAUNA DI EKOSISTEM PERAIRAN BUMANG, PULAU BANGKA - uswatun khasana; Reza, Reza; Akbar, Muhammad Ali; Kurniawan, Ardiansyah; Uswatun Khasana, uswatun khasana (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
This study aims to identify the community structure, conservation value, and habitat suitability of the ichthyofauna in the aquatic ecosystem of the Bumang River, Bangka Island. Exploration was conducted in June–August 2025 using a descriptive exploratory method through fishing with traps, gillnets, and scoop nets at three observation stations. The identification results showed that there were 41 fish species, one shrimp species, one freshwater crab species, and one snail species. Three of them are endemic species of Bangka Island, namely Betta chloropharynx, Parosphromenus bintan, and Betta schalleri. The diversity index (H’) value in the Bumang River ranged from 1.243–2.578 which indicates a moderate category, the evenness index (E) between 0.334–0.694, and the dominance index (C) between 0.114–0.403 which indicates the absence of dominant species. Water quality parameters indicate a temperature of 25–28°C, pH 5–6, and DO 3.7–6.5 mg/L, which are still suitable for freshwater fish life. The presence of several endemic and endangered species such as Betta schalleri (EN), Betta chloropharynx (CR), and Parosphromenus bintan (VU) demonstrates the importance of the Bumang River as an inland water conservation area with high ecological value. The results of this study are expected to become the basis for the sustainable management and protection of aquatic biodiversity on Bangka Island.